HUBUNGAN PENGETAHUAN DAN KEMAMPUAN PERIKSA PAYUDARA SENDIRI (SADARI) DENGAN STADIUM KANKER PAYUDARA DI RSUD ARIFIN ACHMAD PROVINSI RIAU - Yulan Weldiani; Sofiana Nurchayati; Reni Zulfitri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2018)
Breast cancer is a cancer with a high prevalence. Many patients with breast cancer are often found in advanced stages which make the healing process more difficult. This study aims to determine the relationship between knowledge and the ability of breast self-examination (BSE) and breast cancer stage in Oncology Polyclinic of Arifin Achmad Hospital in Riau Province. The design of this research is descriptive correlation with cross sectional approach. There were 30 breast cancer patients taken as the samples using purposive sampling technique. The measuring tool used was a set of observation checklist sheets containing the steps of BSE ability and a questionnaire about knowledge of breast cancer and BSE that has been tested for its validity and reliability. The analyses used were univariate and bivariate analysis. The result of the research showed that the characteristic of the respondents were mostly at the age of 45-55 years old (early elderly) 11 respondents (36.7%), all respondents were female, and their last level of education was primary 13 respondents (43.3%). The majority of the respondents' knowledge fell into a good category where there were 21 respondents (70%), the respondents' ability of doing BSE mostly fell into a not really good category where there were 21 respondents (70%), and the breast cancer stadium of the respondents was at the advanced stage where there were 20 respondents (66.7%). The result of the statistical test shows that there is no correlation between knowledge and breast cancer stage (p-value = 0,204), and there is a relationship between ability of doing breast self-examination with breast cancer stage (p-value = 0,030). It is suggested that nurses should improve educating patients and society to early detect and prevent breast cancer incidence.Keywords: Breast Cancer, Breast Self-Examination (BSE), Knowledge